Penanaman Karakter Nasionalisme Cinta Bahasa Indonesia pada Bulan Bahasa dan Sastra - Intan Kusumawati (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The purpose of this study was to determine the implementation of the cultivation of character education in the value of nationalism through loving Indonesian in the language month at Ngoto Sewon Bantul Elementary School. The nationalism character of Indonesian love is a manifestation of love for the motherland and nation through loving the use of Indonesian as the language of instruction in education in schools and as the language of unity. The purpose of inculcating the character of nationalism is that students love and can use Indonesian properly and correctly as a national language and language that can unite unity and unity in the daily lives of students in the family, school and community. In October the Indonesian nation is celebrated as a month of language and literature, which is a form of love for the motherland and refers to the history of the Indonesian nation and state. Ngoto Sewon Bantul Elementary School as a child rights-based cultural krida school held a series of activities in the form of competitions to commemorate the language and literary month. The implementation activities of the inculcation of character education in the value of nationalism were held several kinds of activities in the form of competitions such as listening to stories, writing short stories, reading poetry, creating poetry, writing poetry, storytelling, singing, speeches, coloring and making posters. The purpose of this language and literary month activity is that students have the character to love language and literature which are the noble values of the Indonesian people that need to be preserved and remain preserved.Keywords: Cultivating the character of nationalism; love the motherland; language and literature.